IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION BERBASIS LKS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KONSEP SISTEM PERNAPASAN KELAS VIII SMP NEGERI 5 AMBON - Yulita Kailola; F Leiwakabessy; Prelly Tuapattinaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: One reason students tend to score below the KKM is the lack of understanding of the material provided by teachers and students less actively involved in the learning process. Method: This research uses Problem Based Instruction (PBI) model and the Student Sheet (LKS) media. This study looks at the improvement of students' learning outcomes on the concept of the VIII grade system of SMP Negeri 5 Ambon by applying the Problem Based Instruction based LKS model. This research was conducted at SMP Negeri 5 Ambon. Result: Implementation of Problem Based Instruction based learning model (LKS) based on LKS can improve biology learning result. Conclusion: Implementation of Problem Based Instruction based learning model can improve student learning outcomes on the concept of Respiratory System of Class VIII4 SMP Negeri 5 Ambon.